384 SHORT-TERM OUTCOMES OF INTRA-THORACIC ESOPHAGO-GASTRIC ANASTOMOSES UNDER MINIMALLY INVASIVE ESOPHAGECTOMY VIA A PRONE POSITION. (17th September 2021) - Mine, Shinji; Watanabe, Masayuki; Kanamori, Atushi; Imamura, Yu; Okamura, Akihiko; Hashimoto, Takashi; Hashiguchi, Tadasuke; Kuniyasu, Tetsushi; Nasu, Motomi; Fujiwara, Daisuke; Ozaki, Asako; Yoshino, Kohei; et al.
Abstract: : Although minimally invasive esophagectomy (MIE) has been performed for esophageal cancer worldwide, intra-thoracic anastomosis under prone positions is still challenging. In this retrospective study, we reviewed our short-term results of this anastomotic technique in our institution. Methods: From November 2016 to December 2019, we performed 319 esophagectomies. Of these patients, 28 patients (9%) underwent intra-thoracic esophago-gastric anastomosis under MIE. Procedures: The left side of an esophageal stump which had been closed using a linear stapler was opened for anastomosis. Then, the anterior wall of a gastric conduit, around 5 cm below the tip, was opened for anastomosis. Linear staplers were inserted in both esophageal stump and gastric conduit and side-to-side anastomosis was performed. The opening for insertion was closed using a hand-sewn anastomosis in 2 layers. Results: Five patients (18%) suffered anastomotic leakage with Clavien-Dindo 2 and 3a, and all of them recovered by conservative treatments. Two patients (2/19, 11%) showed anastomotic stricture which improved by several endoscopic dilatations. Six patients (6/19, 32%) showed the reflux esophagitis of Grade C. Conclusion: Although we have not experienced severe or critical post-operative complications, the short-term results of intra-thoracic anastomosis under MIE were not sufficient. Additional progresses in techniques are required.